In Visioning the City: Urban History Techniques Through Historical Photographs - Mattison, David (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1984)
The past is always present in photographs. Unique visual statements and readily reproducible photographs assist in reconstructing the past through the transmission of information by sight. One of the more important, yet often neglected, areas of scholarship is the documentary photograph taken for or representing a certain place or event in history. Provided its context and accuracy are determined and verified through external evidence, the photograph is primary source material whose judicious use by historians can relay information not available through other kinds of records.